Florida 4-H Officers' Handbook - Tracy Tesdall; Judith Levings; Ali Baker; Sarah Hensley; Stacey Ellison (EDIS)
The duties and responsibilities of each of the club officer roles are outlined in this helpful guide. It also includes a 4-H club meeting checklist and information about club performance recognition. This 15-page fact sheet was revised by Tracy Tesdall, Judith Levings, Ali Baker, Sarah Hensley, Stacey Ellison, and published by the UF Department of 4-H Youth Development, September 2014.